Intergovernmental relations system in the Ethiopian Federation: normative considerations - Nigussie Afesha (Cogent Social Sciences)
The structure and process of intergovernmental relations (IGRs) is a question that all federations must grapple with. Between 1991 and 2019, during the Ethiopian People’s Revolutionary Democratic Front (EPRDF) era, the ruling political coalition was a venue where mutual concerns and misunderstandings between federal and sub-state institutions were managed. However, confining IGR in this way undermined the establishment of formal institutions that would be open to public scrutiny. Following Prime Minister Desalegn’s resignation in 2018, political ruptures occurred within the ruling coalition. The need to formalize the IGR resulted in the 2021 IGR Law. This article examines whether the new law entrenches relevant IGR institutions, whether established IGR forums have the capacity to regularize IGR, and whether established IGR institutions reduce excessive dependence on the party apparatus. This article used a qualitative research approach. This study revealed that most IGR forums remain dysfunctional, and most IGR relations occur informally within intra-party discussions. Although the IGR law contains many provisions, it is largely unimplemented. The dysfunction of IGR forums and their implementation of IGR law are associated with the lack of political commitment by the government to depart from the informal IGR that relied upon the ruling party line to manage government functions, including IGR.